Workshop Bedah Buku “Kajian Kebijakan Politik Internasional: Metode, Teori dan Kasus” di Universitas Panca Marga - Fitria, Nurul Jannah Lailatul; Puspitarini, Renny Candradewi (Universitas Ekuitas Indonesia, 2023)
Community service activities are carried out for 2019 batch students of the Public Administration Study Program, Faculty of Social and Political Sciences, Panca Marga University. This activity is based on the results of observations on partners regarding the urgency of understanding international political policy studies. The method of implementing community service consists of seven stages summarized in pre-activity, during activities, and post-activity. Pre-activities carried out in-depth observations and coordination with competent resource persons as well as authors of International Political Policy Studies books. During the activity, partners were presented with material through power points and interactive communication during material delivery and question and answer sessions. After the activity, partners are still monitored by uploading videos on YouTube accounts and conducting evaluation questions to partners to find out partners' understanding of the workshop material. The advantages of the Book Review Workshop